Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 1 - 1.2 - Linear Equations in One Variable - 1.2 Exercises - Page 87: 43


No Solution

Work Step by Step

Solve : $\frac{x}{x^{2}-3x} + \frac{4}{x} = \frac{1}{x-3}$ $\frac{x}{x(x-3)} + \frac{4}{x} = \frac{1}{x-3}$ Multiplying both sides with x(x-3) x + 4(x-3) = x 4(x-3) = 0 x = 3 Plug x=3 into the expression. Division by zero is undefined, so x=3 is extraneous.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.